Exponential-and-uniform-based video splitting framework in grid environment - Latip, Rohaya; Mien, May Chong; Ibrahim, Hamidah (2014)
Data transmission is the physical transfer of data over apoint-to-point or point-to-multipoint communication channels, such as the copper wires, optical fibers, or wireless communication channels. These transmitted data are included text, audio, video, and image graphics. However, among these data, video is the data that takes up a lot of space for storage and time during the transmission. To solve the storage problem for the large video data, in our paper, we are proposing the Grid-based Video Storage Framework for storing the large video data. In order to reduce the data transmission time, we are also applying our new video splitting technique, which is the “Exponential-and-Uniform-based Splitting Technique” on to the proposed framework. Our Grid based Video Storage Framework is implemented on the Academic Grid Storage Malaysia for storing the video data.